Employee Engagement and Productivity-Evidences from Higher Education Institutions of Telangana State in India - Johar, Damandeep; Santikary, Arijit (The journal of contemporary issues in business and government, 2023)
There are significant researches on Employee productivity as one of the important management concept which is always considered as an important factor to achieve organizational success. Enhancing employee productivity in any organization is required significant amount of attention to understand the key factors that influence employee productivity. This study intended to examine the effect of employee engagement on employee productivity in business education sector. The dimensions of work engagement as vigor, dedication, absorption and career development were used in this study. The primary data using questionnaire were collected from 350 employees of higher education sector from throughout Telangana State by using online survey method. SPSS was used to analyze the collected data. The result indicated that work engagement had significant positive influence on employee productivity however, regression analysis confirmed that all the dimensions of work engagement used in the study does not have equal effect on employee productivity.